ҚАРАҚАЛПАҚ ЭПОСЛАРЫНЫҢ ГЕНЕЗИСИНЕ ТИЙКАР БОЛҒАН СЮЖЕТЛИК МОТИВЛЕР ҲӘМ ОНЫҢ СЫРТ ЕЛ АЛЫМЛАРЫ ТӘРЕПИНЕН ҮЙРЕНИЛИЎИ МӘСЕЛЕЛЕРИ - Алламбергенов, К.; Алламбергенова, Г.К. (FAN va JAMIYAT, 2017)
The article is devoted to one of the actual issues of the Turkic folklore the study of the motives of magic plot as an ideological aesthetic basis in the formation and genesis of Karakalpak epos. The use of the comparative-typological method let the author determine the similarities and differences of these motives with the ethic folklore heritage of the Turkic-Mongolian and Arabian-Persian peoples. The presence of the motives of magic plot in the epic works is explained by their historical-cultural connections and spiritual-cultural similarities of the above-mentioned peoples. The article contains the opinious of foreign scholars on the issue under discussion, based on the comparative-typological research works.